IMPLEMENTATION OF EDUCATIONAL MANAGEMENT STRATEGIES TO IMPROVE THE COMPETITIVENESS OF EDUCATIONAL INSTITUTIONS - Aminullah Aminullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to examine the implementation of educational management strategies to enhance the competitiveness of educational institutions. The focus of the study is directed at how the processes of strategic planning, program implementation, and managerial evaluation can strengthen the competitive advantage of educational institutions. The research method used is a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation studies at several educational institutions. The results indicate that the implementation of a targeted and sustainable management strategy can improve the quality of educational services, organizational effectiveness, and the institution's reputation in the eyes of the public. Successful implementation is strongly influenced by visionary leadership, teacher participation, and innovation in the learning process. The implications of this study emphasize the importance of strengthening a culture of quality, collaboration between stakeholders, and the use of technology as key strategies in enhancing the competitiveness of educational institutions in the global era.